Structural and functional analysis of Escherichia coli membrane disruption by Ib-M peptides - Ana Elvira Farfán-García; Indira Paola Hernández-Peñaranda; Oscar G. Gómez-Duarte; Edgar Javier Rincón-Barón; Gerardo Andrés Torres-Rodríguez; Johanna Marcela Flórez-Castillo (PLoS ONE, 2025)
Antimicrobial resistance represents a critical global public health challenge, leading to increased mortality and morbidity due to the ineffectiveness of current antibiotics against bacterial infections. Antimicrobial peptides (AMPs) offer a promising alternative for treating bacterial infections because of their broad-spectrum activity, biocompatibility, and rapid bactericidal action. Recent studies have demonstrated that Ib-M peptides exhibit bactericidal activity against pathogenic Escherichia coli clinical isolates. The objective of this study was to evaluate the mechanisms by which Ib-M peptides destabilize and disrupts E. coli membranes. We showed by dilutions assays that Ib-M peptides had a minimum inhibitory concentration (MIC) of 12.5 µM against E. coli. Electron microscopy studies confirmed that Ib-M peptides were directly implicated in E. coli membrane disruption, altered bacterial shape and subsequent disintegration. To understand bacterial membrane interaction with Ib-M peptides at the molecular level, we evaluated structure-function relationships using circular dichroism spectroscopy and in silico simulations. These studies demonstrated the strong amphipathic, hydrophobic and cationic properties of Ib-M peptides. At sublethal concentrations, these peptides interacted with bacterial lipopolysaccharides (LPS), leading to outer and inner membrane permeation and cytoplasmic membrane depolarization. This effect was transient at sublethal Ib-M peptides concentrations, as evidenced by the recovery of bacterial growth in lag phase kinetics. At higher concentrations, there was high depolarization of cytoplasmic membrane, disruption of outer membrane and inner membranes and irreversible bacterial lysis. When mammalian cells were exposed Ib-M1 peptide cytotoxic effect was only reached when MIC was increased 10-fold. In conclusion, Ib-M peptides inhibited E. coli growth by disrupting bacterial membranes via interactions with LPS and increased membrane permeation yet, they have low cytotoxicity on mammalian cells. This study highlights the mechanisms of action on Ib-M peptides as antimicrobials and paves the way for further research on the clinical use of these peptides as antimicrobial agents against multidrug resistant bacterial infections.